Design, construction and performance evaluation of a drip irrigation system (2004)
A gravitational drip irrigation system was designed and constructed using available materials; and tested for the use of small-scale farmers. The system has 4 laterals each 4m long, with each of the laterals having pressure-compensating emitters. This was evaluated based on its efficiency. Tests show that discharge per lateral is 8 1/hr And each of the emitters can deliver 2.1 1/hr with an operating head of 0.97m. The crop water requirement was based on the evapotranspiration rate for Ibadan climatic zone that was given as 5 mm/day. Water conveyance efficiency was 99%; Application efficiency approximates to 94.5% while overall system efficiency was 94.05 %. These results corroborate with Jess (2001) who put the overall efficiency of drip irrigation system at 90 % and above. The total cost of ownership was estimated at N10,030 while the total operating and maintenance cost was N308, as at February 2004.The efficiency of the system coupled with the cost of installation, maintenance and repair show that it is cost effective and viable.